2023
DOI: 10.32473/edis-an267-2023
|View full text |Cite
|
Sign up to set email alerts
|

Converting the Beef Cow Herd to a Controlled Breeding Season

Abstract: This report aims to provide guidance to producers on practical aspects for moving from a system with no defined breeding season to a system with a defined season. Written by Mario Binelli, Thiago Martins, Tim Wilson, Cindy Sanders, Mark Warren, Matt Hersom, and Curt Lacy, and published by the UF/IFAS Department of Animal Sciences, revised January 2023.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In beef cattle herds, it is recommended to control the seasonality of breeding. A controlled calving season is more profitable for beef cattle farmers than year-round calving, as nutrition can be adjusted according to physiological needs [ 7 , 17 ]. The difficulty of calving can be monitored; calves will be more uniform in weight and age, and cows with reproductive disorders will be easier to identify [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In beef cattle herds, it is recommended to control the seasonality of breeding. A controlled calving season is more profitable for beef cattle farmers than year-round calving, as nutrition can be adjusted according to physiological needs [ 7 , 17 ]. The difficulty of calving can be monitored; calves will be more uniform in weight and age, and cows with reproductive disorders will be easier to identify [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A controlled calving season is more profitable for beef cattle farmers than year-round calving, as nutrition can be adjusted according to physiological needs [7,17]. The difficulty of calving can be monitored; calves will be more uniform in weight and age, and cows with reproductive disorders will be easier to identify [17]. Previous research has shown the influence of calving season on calving traits.…”
Section: Introductionmentioning
confidence: 99%